Leadership Supervision of Teacher Performance Management in the Learning Process in Secondary Schools - Tukiyo; Arianto, Sofyan; Haryono, Purwo; Riyadi, Iswan (Jurnal Pedagogi dan Pembelajaran, 2024)
The principal did not carry out the task of supervising teacher teaching optimally and the supervision carried out was more bureaucratic and autocratic, emphasizing hierarchy. Another fact is that 44% of teachers do not like the supervision carried out in the classroom by both the principal and his deputy, and 5.88% of secondary school teachers do not agree with teaching observations. This is urgent to conducted research because there is a difference between theory and reality. This research aimed to analyze the effect of supervision on the teaching performance of teachers in secondary schools. Methods in quantitative research. The subjects were 33 secondary school teachers. The data collection technique uses a set of teaching and learning observation instruments that have been adapted and used by all schools to assess and manage educational programs. Analysis techniques, teacher teaching performance is measured based on Daily Learning Plans, induction tools, teaching delivery, questioning techniques, student involvement, reinforcement, student training, and assignments, checking student training and assignments, learning closure, and classroom management before and after clinical supervision. The results found in this research indicate that teachers in schools experience deficiencies in planning learning in the classroom. It was found that clinical supervision also helps teachers improve the teaching and learning process more effectively so that teaching can improve student mastery. Conclusion, Clinical supervision can be used as a guide for teachers and students in secondary schools to improve knowledge. The research implications provide a complete picture of clinical supervision in improving student preparation and knowledge.